2020
DOI: 10.3390/cells9041012
|View full text |Cite
|
Sign up to set email alerts
|

Potency and Selectivity of SMAC/DIABLO Mimetics in Solid Tumor Therapy

Abstract: Aiming to promote cancer cell apoptosis is a mainstream strategy of cancer therapy. The second mitochondria-derived activator of caspase (SMAC)/direct inhibitor of apoptosis protein (IAP)-binding protein with low pI (DIABLO) protein is an essential and endogenous antagonist of inhibitor of apoptosis proteins (IAPs). SMAC mimetics (SMs) are a series of synthetically chemical compounds. Via database analysis and literature searching, we summarize the potential mechanisms of endogenous SMAC inefficiency, degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 154 publications
(146 reference statements)
0
29
0
Order By: Relevance
“…When cells are stimulated by apoptosis, mitochondria release Smac protein into the cytoplasm to bind to IAPs, making it lose the inhibition of caspase activity and subsequently promote cell apoptosis. 11 , 20 , 34 Three previous papers published in Cell 35 , 36 , 37 have reported that Smac mimetics can induce auto‐ubiquitination and cIAP1/2 degradation through different mechanisms, leading to tumour necrosis‐factor‐alpha‐mediated cancer cell death. 38 These studies have prompted the introduction of Smac mimetics in anti‐cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…When cells are stimulated by apoptosis, mitochondria release Smac protein into the cytoplasm to bind to IAPs, making it lose the inhibition of caspase activity and subsequently promote cell apoptosis. 11 , 20 , 34 Three previous papers published in Cell 35 , 36 , 37 have reported that Smac mimetics can induce auto‐ubiquitination and cIAP1/2 degradation through different mechanisms, leading to tumour necrosis‐factor‐alpha‐mediated cancer cell death. 38 These studies have prompted the introduction of Smac mimetics in anti‐cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to augmenting SMAC mimetic-induced apoptosis, TNF-α could have broader effects on the immune system by stimulating cytotoxic T cells to act against cancer cells [ 36 ]. Previous work supported testing birinapant in combination with immune checkpoint inhibitors [ 5 , 37 , 38 ]. Our new findings suggested that the addition of docetaxel could further sensitize cancer cells to treatment with SMAC mimetics and immune checkpoint inhibitors, which is currently under active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent inappropriate activation of these pathways, cell death is strictly regulated by both pro-apoptotic and anti-apoptotic proteins. Inhibitor of apoptosis (IAP) proteins are one such regulator that block executioner caspase function [ 5 ]. Second mitochondrial activator of caspases (SMAC) proteins, on the other hand, antagonize IAP proteins, thereby promoting cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Smac release from mitochondria [138]. Increase tumor cells sensitivity to granzyme-induced apoptosis.…”
Section: Radiation-induced Effectmentioning
confidence: 99%